2022
DOI: 10.3389/fpsyg.2022.920556
|View full text |Cite
|
Sign up to set email alerts
|

The Link Between Energy-Related Sensations and Metabolism: Implications for Treating Fatigue

Abstract: Energy-related sensations include sensation of energy and fatigue as well as subjective energizability and fatigability. First, we introduce interdisciplinary useful definitions of all constructs and review findings regarding the question of whether sensations of fatigue and energy are two separate constructs or two ends of a single dimension. Second, we describe different components of the bodily energy metabolism system (e.g., mitochondria; autonomic nervous system). Third, we review the link between sensati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
1
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 230 publications
0
15
1
1
Order By: Relevance
“…Direct actions of cannabinoids on respiratory complexes have been described [ 35 ] independently of their action on mitochondrial cannabinoid receptors [ 22 ]. In particular, several studies have reported specific actions of THC and CBD on mitochondrial respiratory chain activity, ROS production and cellular integrity, promoting toxicological effects in certain cells that may be potentially relevant for clinical populations [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…Direct actions of cannabinoids on respiratory complexes have been described [ 35 ] independently of their action on mitochondrial cannabinoid receptors [ 22 ]. In particular, several studies have reported specific actions of THC and CBD on mitochondrial respiratory chain activity, ROS production and cellular integrity, promoting toxicological effects in certain cells that may be potentially relevant for clinical populations [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…These higher-order sensations are composed of many lower-level sensations such as visual, auditory, olfactory or bodily experiences (Nummenmaa et al, 2018). Energy-related sensations include the sensation of fatigue (synonyms: exhaustion, weariness) and of energy (synonyms: vigour, vitality) (Filippi et al, 2022). These sensations can refer to different domains, such as physical, cognitive, emotional, social, motivational and sexual fatigue or energy sensations (Filippi et al, 2022).…”
Section: Psychedelics Mitochondria and Energy-related Sensationsmentioning
confidence: 99%
“…Energy-related sensations include the sensation of fatigue (synonyms: exhaustion, weariness) and of energy (synonyms: vigour, vitality) (Filippi et al, 2022). These sensations can refer to different domains, such as physical, cognitive, emotional, social, motivational and sexual fatigue or energy sensations (Filippi et al, 2022). Importantly, mounting evidence suggests that mitochondrial bioenergetics underlie the sensation of energy and fatigue (Filippi et al, 2022; Filler et al, 2014; Karabatsiakis et al, 2014).…”
Section: Psychedelics Mitochondria and Energy-related Sensationsmentioning
confidence: 99%
See 2 more Smart Citations